Performance Analysis of Ceramic Membranes in Clean Water Treatment on River Water Quality - Yogi Astrada; Muhammad Faizal; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The clean water treatment process changes the physical, chemical, and biological properties of water so that it meets the requirements for use as drinking water or daily needs. The purpose of this research is to analyze the performance of ceramic membranes in processing water from the Kelekar River into clean water using an environmentally friendly microfiltration–adsorption–ceramic membrane integrated process. The research was carried out from January to April 2022 at the Chemical Engineering Laboratory of the Sriwijaya Polytechnic. The sampling location for this research is Kelekar River, Karang Raja Village, East Prabumulih. The main tools and materials are a series of water filters (microfiltration–adsorption–ceramic membrane) and river water. The analysis results show that a series of microfiltration-adsorption-ceramic membrane integrated process water treatment equipment can be used to treat river water into clean water. Based on the analysis of river water quality parameters, such as BOD5, iron (Fe), manganese (Mn), nitrate (NO3-), ammonia (NH3-N), and total coliform bacteria after water treatment were within environmental quality standards. Meanwhile, COD and nitrite (NO2-) were still not meeting the environmental quality standards set by Government Regulation of Republic Indonesia No. 22 of 2021 concerning the implementation of environmental protection and management.